Closed-Circuit Television Testimony: Liveness and Truth-telling - Kathryn Leader (Law Text Culture, 2010)
A witness who gives evidence orally demonstrates, for good or ill, more about his or her credibility than a witness whose evidence is given in documentary form. Oral evidence is public; written evidence may not be. Oral evidence gives to the trial the atmosphere which, though intangible, is often critical to the jury’s estimate of the witness. Butera v DPP (Vic) (1987) The legal arena may be one of the few remaining cultural contexts in which live performance is still considered essential (Auslander 1999: 9).